Barriers to implementation of STRIDE, a national study to prevent fall‐related injuries. Issue 5 (13th February 2021) - Reckrey, Jennifer M.; Gazarian, Priscilla; Reuben, David B.; Latham, Nancy K.; McMahon, Siobhan K.; Siu, Albert L.; Ko, Fred C.
Abstract: Background/Objectives: Evaluations of complex models of care for older adults may benefit from simultaneous assessment of intervention implementation. The STRIDE (Strategies To Reduce Injuries and Develop confidence in Elders) pragmatic trial evaluated the effectiveness of a multifactorial intervention to reduce serious fall injuries in older adults. We conducted multi‐level stakeholder interviews to identify barriers to STRIDE intervention implementation and understand efforts taken to mitigate these barriers. Design: Qualitative interviews with key informants. Setting: Ten clinical trial sites affiliated with practices that provided primary care for persons at increased risk for fall injuries. Participants: Specially trained registered nurses working as Falls Care Managers (FCMs) who delivered the intervention ( n  = 13 individual interviews), Research Staff who supervised trial implementation locally ( n  = 10 group interviews, 23 included individuals), and members of Central Project Management and the National Patient Stakeholder Council who oversaw national implementation ( n  = 2 group interviews, six included individuals). Measurements: A semi‐structured interview guide derived from the consolidated framework for implementation research (CFIR). Results: We identified eight key barriers to STRIDE intervention implementation. FCMs navigated complex relationships with patients and families while working with Research Staff to implement the intervention in primary care practices with limited clinical space, variable provider buy‐in, and significant primary care practice staff and provider turnover. The costs of the intervention to individual patients and medical practices amplified these barriers. Efforts to mitigate these barriers varied depending on the needs and opportunities of each primary care setting. Conclusion: The many barriers to implementation and the variability in how stakeholders addressed these locally may have affected the overall STRIDE intervention's effectiveness. Future pragmatic trials should incorporate simultaneous implementation aims to better understand how research interventions translate into clinical care that improves the lives of older adults.